2018
DOI: 10.1111/gcb.14132
|View full text |Cite
|
Sign up to set email alerts
|

Tree mycorrhizal type predicts within‐site variability in the storage and distribution of soil organic matter

Abstract: Forest soils store large amounts of carbon (C) and nitrogen (N), yet how predicted shifts in forest composition will impact long-term C and N persistence remains poorly understood. A recent hypothesis predicts that soils under trees associated with arbuscular mycorrhizas (AM) store less C than soils dominated by trees associated with ectomycorrhizas (ECM), due to slower decomposition in ECM-dominated forests. However, an incipient hypothesis predicts that systems with rapid decomposition-e.g. most AM-dominated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
154
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(169 citation statements)
references
References 101 publications
(202 reference statements)
14
154
1
Order By: Relevance
“…These results were recently extrapolated to all terrestrial biomes, further suggesting that AM‐dominated forest ecosystems store more carbon in aboveground biomass, whereas EcM‐dominated systems store more carbon in soil (Soudzilovskaia et al ., ). However, three recent North American temperate forest studies revealed no overall mycorrhizal‐type effect (Zhu et al ., ), opposite trends in deep soil (Craig et al ., ), or an interplay between forest type, mycorrhizal type and soil depth (Jo et al ., ).…”
Section: Soil Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were recently extrapolated to all terrestrial biomes, further suggesting that AM‐dominated forest ecosystems store more carbon in aboveground biomass, whereas EcM‐dominated systems store more carbon in soil (Soudzilovskaia et al ., ). However, three recent North American temperate forest studies revealed no overall mycorrhizal‐type effect (Zhu et al ., ), opposite trends in deep soil (Craig et al ., ), or an interplay between forest type, mycorrhizal type and soil depth (Jo et al ., ).…”
Section: Soil Processesmentioning
confidence: 99%
“…Acidification dramatically reduces the abundance of earthworms (Phillips & Fahey, 2006) that play critical roles in soil aeration, litter fragmentation and transportation into deeper soil horizons. This certainly contributes to the development of deep litter layers in many EcM-dominated ecosystems and may explain relatively low rates of C sequestration in mineral soil (Craig et al, 2018;Zhu et al, 2018).…”
Section: (3) Soil Carbon Cyclingmentioning
confidence: 99%
“…In the rhizosphere, sugars and amino acids exuded by roots can release SOM from mineral associations, allowing for microbial processing and turnover of previously adsorbed compounds (Keiluweit et al, 2015). However, the high-quality substrates exuded into the rhizosphere also promote the production of large quantities of microbial necromass, which can be readily converted into stable MAOM and aggregates (Knicker, 2011;Cotrufo et al, 2013;Schrumpf et al, 2013;Craig et al, 2018). The balance of decomposition and formation of MAOM in the rhizosphere appears to produce a net increase in stable MAOM, likely because root exudates provide plenty of C and nutrients for sorption .…”
Section: Stabilization Of Mineral-associated Organic Mattermentioning
confidence: 99%
“…We collected all soil from Lilly-Dickie Woods in Brown County, Indiana, USA (39 • 14 N, 86 • 12 W; altitude 290 m). For detailed description of the soil and microbial community properties of these soils see Cheeke et al (2017) and Craig et al (2018). Within this forest, we selected from two stands with either >90% basal area of AM-associated or ECMassociated tree species.…”
Section: Experimental Set-upmentioning
confidence: 99%